Impact of managerial performance and its antecedents on vat collection performance to support economy development in UAE - Fakhari, Nabil Yousuf Mohammad (2023)
VAT collection is a major issue for several governments around the world. Different countries have applied different techniques to enhance VAT collection. Likewise UAE government has introduced VAT and its collection is challenging for them. One of the major issues that has been observed in the literature is that support services are limited, and the staff appointed for collection is incompetent and require proper training. Similarly the managerial role at the same time cannot be ignored. Therefore, the purpose of the study is to identify the mediating role of managerial performance between administrative policies, organizational structure, enforcement, staff competence, support services and VAT collection performance. For the said purpose 364 employees of federal tax authority in UAE in general and Dubai and Abu Dhabi in particular were chosen as a respondent. The study is based on primary research and followed a quantitative research approach using causal study technique. The study followed simple random sampling and applied structural equation modeling to test the direct and indirect effects. The findings of the study are based on structural equation modeling technique and contributed to Economic Theory of Tax Compliance by identifying the mediating role of managerial performance. The results revealed that administrative policies, organizational structure, enforcement, staff competence, support services have a significant direct effect over VAT collection performance. Likewise managerial competence significantly mediate the relationship between administrative policies, organizational structure, enforcement, staff competence, support services and VAT collection performance. The study is equally important for the practitioners in understanding the importance of boosting staff competence and provision of support services for enhancing VAT collection.